Engaging students with self-assessment and tutor feedback to improve performance and support assessment capacity - McKevitt, Conor (Journal of University Teaching and Learning Practice, 2016)
Assessment is one of the most important elements of student life and significantly shapes their learning. Consequently, tutors need to ensure that student awareness regarding assessment is promoted. Students should get the opportunity to practise assessing work and receive tutor feedback so that they might improve on both the work and their assessment of it. The purpose of this paper is to investigate how student engagement with criteria, exemplars, self-assessment, and feedback influenced students’ performance, their assessment capacity, and also how students experienced the process. A mixed methods approach was used. Students’ performance and assessments were established using a rubric that included 5 criteria each evaluated using 5 point likert scale linked to descriptors. A thematic analysis of the focus group resulted in two themes. The findings show that overall students’ performance in the assignment significantly improved between draft and final submissions. Students’ assessment of their work significantly differed to the tutor’s on some criteria at both submissions but in opposite directions on one criterion between both submissions. The focus group found that the rubric guided students to produce their draft while tutor feedback guided them to improve on it. However, these findings require further investigation. The following recommendations ensue from the research and should assist student development concerning assessment. Tutors should give students an opportunity to assess work and also see tutor’s assessment of that work using the same criteria. Also, tutors should provide constructive feedback during an assignment.